Upaya Meningkatkan Pendidikan Karakter melalui Sosialisasi dalam Mewujudkan SDGs di SDN Trowulan - Amilia Putri Puspita Sari; Cahyani Dwi Novianti; Munika, Rafilah; Rendi Robintang Siregar; Yosep Salfaridus Nong Sandro; Adinda Aulia Rachma; Husna Zaka Anshori; Mutiara Nabilah Ramadhani; Risti Wahyuningsih; Vena Tri Pramita (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Students of Community Service Program Bela Negara Universitas Pembangunan Nasional “Veteran” Jawa Timur (UPNVJT) Group 9 Trowulan socialize character education by focusing on six steps of washing hands with soap, four miraculous words, anti-bullying, and cultural promotion objects. The purpose of the material selection is to support the development of children's character and childhood early on, which is in line with the purpose of sustainable development in improving quality education. Participants of socialization are students of class 4, 5, and 6 in SDN Trowulan, Mojokerto. The method used through three stages consisting of preparation stages, implementation stages, and post-stage. These three stages prioritize improving character education in children's elementary schools through the work programs that have been designed.